2015
DOI: 10.1007/s11604-015-0471-9
|View full text |Cite
|
Sign up to set email alerts
|

Added value of a single-energy projection-based metal-artifact reduction algorithm for the computed tomography evaluation of oral cavity cancers

Abstract: The SEMAR significantly improved the oral cavity cancer visualization and diagnostic confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The dedicated metal artifact reduction technique, the single-energy metal artifact reduction (SEMAR, Toshiba Medical Systems) algorithm, was also introduced on 320-row CT scanners and studies showed that its application significantly reduced artifacts due to various metallic objects (e.g. dental metals (15,16), metallic coils (17) and hip prostheses (18)).…”
Section: Introductionmentioning
confidence: 99%
“…The dedicated metal artifact reduction technique, the single-energy metal artifact reduction (SEMAR, Toshiba Medical Systems) algorithm, was also introduced on 320-row CT scanners and studies showed that its application significantly reduced artifacts due to various metallic objects (e.g. dental metals (15,16), metallic coils (17) and hip prostheses (18)).…”
Section: Introductionmentioning
confidence: 99%
“…11 Metal artefact was reported to be reduced in neck CT with SEMAR. 15,16 However, these reports on SEMAR evaluated images reconstructed from volume scan data. 15,16 Because a 16-cm range of z-axis can be covered with a single volume scan using 320-detector row CT, clinical applicability of a volume scan has been limited.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual monochromatic image with a high keV, which is derived from dual-energy CT, is reported to be helpful in reducing metal artefacts; however, dual-energy CT requires a specific CT scanner and scanning protocol. 9,10 At the reconstruction step, 11 metal-implanting methods [12][13][14][15][16] or iterative reconstruction algorithms 17,18 are available to reduce metal artefacts. Single-energy metal artefact reduction (SEMAR) for helical scan data is a metal-implanting method and the forward-projected model-based iterative reconstruction solution (FIRST) is a full iterative reconstruction algorithm, and both have become available recently.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, so far the evidence shows that high energy DECT VMIs are promising and have the potential for improving lesion assessment in areas obscured by artifact, such as the oral cavity. Further refinements in applications of DECT for artifact reduction, and how they compare to other methods that are being developed using SECT [ 60 , 63 ], are an interesting topic for future research.…”
Section: Dental Artifactmentioning
confidence: 99%